Penolakan Terhadap Agama Materialisme: Sejarah, Perkembangan, Kritikan - Ardiansyah Siregar (Jurnal Penelitian Multidisiplin, 2022)
There is a school of philosophy that rejects religion, this school provides the view that what can be said to really exist is matter. Thus, religion that contains elements of the unseen is rejected in their view. This understanding is known as 'materialism'. This school can be said to be atheist because they reject supernatural things such as God, angels, heaven and hell. Studying materialism is very urgent for the survival of human life so that no one is affected by materialism. The formulation of the problem being studied is why does materialism exist? What is the development of materialism like? How is the argumentation of materialism in rejecting religion? The purpose of this study is to prevent and deal with the notion of materialism for human life. The method used in this study is a qualitative method with a 'library research' approach. The conclusion of this study will lead the readers that materialism as an ideology that rejects religion should be avoided